The Influence of The Use of Direct Method in Teaching Reading Comprehension and The Students' Achievement - Lukma Nul Hakim (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2019)
Direct method of teaching is a systematic instructional method that first and foremost requires the teacher to have a command of the subject matter at as close to mastery level as possible. This means that whether subject matter is at the elementary level, middle school level, high school level, college level or adult education level, the teacher thoroughly